The Do-Well study: protocol for a randomised controlled trial, economic and qualitative process evaluations of domiciliary welfare rights advice for socio-economically disadvantaged older people recruited via primary health care - Haighton Catherine; Moffatt Suzanne; Howel Denise; McColl Elaine; Milne Eugene; Deverill Mark; Rubin Greg; Aspray Terry; White Martin (BMC, 2012)
Abstract Background Older people in poor health are more likely to need extra money, aids and adaptations to allow them to remain independent and cope with ill health, yet in the UK many do not claim the welfare benefits to which they are entitled. Welfare rights advice interventions lead to greater welfare income, but have not been rigorously evaluated for health benefits. This study will evaluate the effects on health and well-being of a domiciliary welfare rights advice service provided by local government or voluntary organisations in North East England for independent living, socio-economically disadvantaged older people (aged ≥60 yrs), recruited from general (primary care) practices. Methods/Design The study is a pragmatic, individually randomised, single blinded, wait-list controlled trial of welfare rights advice versus usual care, with embedded economic and qualitative process evaluations. The qualitative study will examine whether the intervention is delivered as intended; explore responses to the intervention and examine reasons for the trial findings; and explore the potential for translation of the intervention into routine policy and practice. The primary outcome is the effect on health-related quality of life, measured using the CASP 19 questionnaire. Volunteer men and women aged ≥60 years (1/household) will be identified from general practice patient registers. Patients in nursing homes or hospitals at the time of recruitment will be excluded. General practice populations will be recruited from disadvantaged areas of North East England, including urban, rural and semi-rural areas, with no previous access to targeted welfare rights advice services delivered to primary care patients. A minimum of 750 participants will be randomised to intervention and control arms in a 1:1 ratio. Discussion Achieving a trial design that is both ethical and acceptable to potential participants, required methodological compromises. The choice of follow-up length required a trade-off between sufficient time to demonstrate health impact and the need to allow the control group access to the intervention as early as possible. The study will have implications for fundamental understanding of social inequalities and how to tackle them, and provides a model for similar evaluations of health-orientated social interventions. If the health benefits of this intervention are proven, targeted welfare rights advice services should be extended to ensure widespread provision for older people and other vulnerable groups. Current Controlled Trials ISRCTN Number ISRCTN37380518